2018
DOI: 10.1016/j.sjbs.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the factors that influence the career specialty preferences by the undergraduate medical students

Abstract: It is often perceived that undergraduate medical students do not select their career specialty until they are graduated. This study aimed to probe the preferences of undergraduate medical students about their career specialty and the factors influencing their choices. A self-administered questionnaire was distributed to 3rd through 5th year undergraduate medical students to record their choices of specialties and to identify the factors that influence their career selection. Out of 220 respondents, 29 (13.2%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 42 publications
8
29
3
4
Order By: Relevance
“…According to FM specialty, the present work showed that only 6% of students chose it as a future career, where it ranked the tenth among eleven specialty options given (Figure 1). This result goes along with that observed in a recent Saudi study done on 220 medical students of Taibah University, where only 6.8% of students chose FM (33).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to FM specialty, the present work showed that only 6% of students chose it as a future career, where it ranked the tenth among eleven specialty options given (Figure 1). This result goes along with that observed in a recent Saudi study done on 220 medical students of Taibah University, where only 6.8% of students chose FM (33).…”
Section: Discussionsupporting
confidence: 89%
“…The most common specialties chosen by students in the present study were internal medicine, surgery, dermatology and pediatrics. The same result was observed in another two Saudi studies (32,33). This result was also reported by medical students in other international studies where surgery, general medicine and pediatrics were the most chosen specialties by surveyed medical students (34).…”
Section: Discussionsupporting
confidence: 87%
“…Students may be urged to change their choice of specialty after spending few years in training. Such mishaps, primarily due to careless career selection, jeopardize the efforts and undermine the entire process of intended delivery of appropriate health-care services to the community (Guraya & Almaramhy, 2018). Historically, it is noted that medical student's preferences for specialty choice, as well as their motivational factors for a career choice have a tendency to change during the period of their studies.…”
Section: Introductionmentioning
confidence: 99%
“…The environment in which students observe their lecturers practicing; the enjoyment the lecturers seem to derive from practicing, or the difficulty in which they practice, can form the basis for choices made by the young, impressionable students. Fewer graduates will choose a specialty as a career if the specialty does not appear attractive at the time of their clinical placement during training, in terms of flexible working hours, availability of equipment and supplies and practice satisfaction (28)(29)(30)(31). In a study done in Ethiopia, students preferred not to specialise in particular disciplines because of observed shortages of equipment and supplies at the workplace (15).…”
Section: The Learning Experiences Career Choicesmentioning
confidence: 99%